Goods and Services Tax and Its Impact on Indian Economy: A Study on the Impact of Goods and Services Tax on the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The research paper is regarding impact of GST on Indian Economy. With the introduction of GST there is a condition chaos and confusion among common man. The aim this research paper is to explain the mechanism of GST and its effects on Indian economy. The concept of Goods and Service Tax popularly known as GST was introduced on 1st July, 2017. The GST will have a ‘dual’ structure, which means it will have two components- the Central GST and the State GST. GST is expected to simplify tax administration, ensure ‘Ease of Doing Business’ and promote ‘Make in India.’ On bringing GST into practice, there would be amalgamation of Central and State taxes into a single tax payment. It would also enhance the position of India in both, domestic as well as international market.